Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Hasil Belajar Siswa Kelas V Sekolah Dasar - Ayu Mitha Apriliyah; Iqnatia Alfiansyah; Nataria Wahyuning Subayani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the effect of the cooperative learning model of the Teams Games Tournament (TGT) type on the learning outcomes of fifth-grade elementary school students. The research method used was experimental with a quasi-experimental approach. The research design employed was a non-equivalent control group design. The study involved two classes: the experimental class (VA), which was taught using the Teams Games Tournament (TGT) cooperative learning model, and the control class (VB), which was taught without using the TGT model. The sample consisted of 50 students from classes VA and VB at SD YPI Darussalam. The data collection technique used was a learning outcomes test, designed to measure students’ mastery of the learning material. Data analysis was conducted using the Independent Sample T-test to determine differences in learning outcomes between the two groups. The analysis results showed a Sig. (2-tailed) value of 0.000 ≤ 0.05, which is less than the significance threshold of 0.05. Therefore, H₀ was rejected and Hₐ was accepted, indicating that the cooperative learning model of the Teams Games Tournament (TGT) type has a significant effect on students’ learning outcomes. The findings of this study highlight that the TGT model can create an engaging and competitive learning atmosphere, enhancing student participation and motivation in the learning process. Furthermore, the structured stages in the TGT model—comprising presentation, group formation, game sessions, and tournaments—allow students to interact more actively, share knowledge, and strengthen their understanding of the material collaboratively. Thus, the implementation of the Teams Games Tournament (TGT) cooperative learning model is recommended as an effective alternative strategy for improving learning outcomes in elementary schools, especially for fifth-grade students.